Effect of wood kraft pulp feed on digestibility, ruminal characteristics, and milk production performance in lactating dairy cows. (16th December 2018) - Nishimura, Keiko; Kurosu, Kazuhiro; Terada, Fuminori; Mizuguchi, Hitoshi; Sato, Shigeru; Kushibiki, Shiro
Abstract: The effect of wood kraft pulp (KP) feed on dietary digestibility, ruminal fluid pH, rumen fermentation characteristics, and milk production performance in lactating dairy cows was examined. Four lactating dairy cows were used for the feeding experiment by the cross‐over design. The control group and KP group were set up as treatments. The control group was fed total mixed ration (TMR) (40% roughage and 60% concentrate) and the KP group was fed TMR containing 12% KP that replaced half of the rolled corn in the control diet. The dry matter intake, digestibility of the feed components, and milk yield were not significantly different between control group and KP group. The number of times that the ruminal fluid pH was below 6.1 tended to decrease in the KP group compared to the control group ( p  <   0.10). The acetic acid ratio in the ruminal fluid of the KP group increased compared to the control group ( p  <   0.05) and the propionic acid ratio in the ruminal fluid of the KP group decreased compared to the control group ( p  <   0.05). The acetate:propionate acid ratio was increased in the KP group compared with the control group ( p  <   0.05). Lipopolysaccharide levels in the ruminal fluid of the KP group tended to decrease compared to the control group ( p  <   0.10). Based on these results, it was indicated that the use of KP feed for lactating dairy cows induced the same rumen fermentation characteristics as those in cows given a large amount of roughage without depressing milk productivity. Therefore, KP could be a valuable feed resource substitute for grains, which would also reduce the risk for subacute rumen acidosis.